Exercise adherence and suicidal ideation of Chinese college students: a chain mediation model test - Xing, Zhi; Guo, Kelei; Hui, Zhen; Ma, Qishuai (Frontiers in Psychology, 2023)
Objective: The purpose of this study was to explore the relationship between exercise adherence and suicidal ideation in college students, as well as the mediating role of meaning in life and internet addiction. Methods: A total of 1925 college students (M age = 19.51 years, SD age = 2.393 years) were recruited by stratified cluster sampling method in Zhaoqing University, among which 890 were males and 1035 were females. Exercise adherence, meaning in life, internet addiction and suicidal ideation were assessed by using standard scales. Data were analyzed by Pearson Correlation Analysis, and bias-correction percentile Bootstrap method. Results: (1) There is a significant correlation between exercise adherence, meaning in life, internet addiction and suicide ideation; (2) meaning in life plays a significant mediating role between exercise adherence and suicidal ideation; internet addiction plays a significant mediating role between exercise adherence and suicidal ideation; meaning in life and internet addiction play a chain mediating role between exercise adherence and suicide ideation. Conclusion: Exercise adherence can not only directly predict college students' suicidal ideation, but also indirectly predict college students' suicidal ideation through the independent mediation and chain mediation of meaning in life and internet addiction.